'I wanted to be white': understanding power asymmetries of whiteness and racialisation. Issue 2 (3rd July 2021) - Ortega, Yecid
ABSTRACT: This article uses a self-reflective autoethnography to critique colonisation and whiteness as systems of marginalisation and racialisation. I examine concepts grounded in post-colonial and anti-racist theories, and I interweave these with my experiences in white spaces in Colombia, the USA and Canada as an educator and researcher. I provide personal examples as data to explain how colonisation and whiteness have paved the road to my professional 'success', and I also illuminate how these have taken me away from understanding my cultural and linguistic roots. Contrary to conventional wisdom that formal education is empowering for racialised peoples, this article asserts that critical education has been fundamental to challenge inequality and power asymmetries. Finally, in reflecting on the depths to which whiteness has been entrenched in all aspects of my life and other racialised peoples, I seek determination and liberation by calling into question the normative historical raciolinguistic ideologies of whiteness.